Biological, physical, and chemical properties of wallostonite-added β-SiAlON ceramics. Issue 12 (15th June 2022) - Zhang, Liguo; Ji, Yun; Mu, Jinghua; Ma, Xin; Wang, Lulu; Chang, Guanglei; Xu, Enxia; Liu, Xinhong; Yuan, Huiyu; Cui, Junyan; Gao, Jinxing
Abstract: The different content of wollastonite was added to raw materials to prepare β-SiAlON ceramics; furthermore, in this study, the effect of wollastonite on the physical, chemical, and biological properties of β-SiAlON was explored. X-ray diffraction and scanning electron microscopy (SEM) demonstrated that Ca in β-SiAlON was uniformly distributed; however, the addition of wollastonite did not lead to the formation of the Ca-α-SiAlON phase. Wollastonite addition improved the sintering performance and increased the compressive strength of β-SiAlON ceramics. Moreover, SEM demonstrated that by adding wollastonite, the bonding of the sample became tighter. Ion release results demonstrated that the material had low ion release and stable chemical properties. Moreover, in cellular experiments, when the content of wollastonite is <12 wt% in β-SiAlON ceramics, β-SiAlON ceramics with or without Ca demonstrated satisfactory biocompatibility. The presence of some amount of Ca did not affect the adhesion, spreading, and proliferation of the MC3T3-E1 cells. Moreover, when wollastonite is <12 wt%, culturing MC3T3-E1 cells in the leaching solution of β-SiAlON ceramics confirmed that bone formation is unaffected. Thus, β-SiAlON ceramics containing Ca (wollastonite <12 wt%) demonstrated good physical and chemical properties; however, the biological properties remain unaffected. Therefore, the ceramics that were prepared are bioactive materials having excellent properties.